PERILAKU NYERI NEUROPATIK DAN EKSPRESI VOLTAGE GATE SODIUM CHANNEL PADA TIKUS SPRAGUE DAWLEY PASCALIGASI NERVUS SPINALIS LUMBAL 5, DENGAN ATAU TANPA METILKOBALAMIN - , ENDANG MUTIAWATI RAHAYUNINGSIH ([Yogyakarta] : Fakultas Kedokteran UGM, 2012)
Neuropathic pain is an expression of the nerve damage that impaired its excitability, such as increased excitability in the nerve lesion and surrounding healthy nerves as well (Gold et al., 2003). It is estimated that the incidence of neuropathic pain ranges between 2-40% of all adult men. Some neuropathic pain can not be cured, such as in patients with diabetes mellitus, trigeminal neuralgia, cervical syndrome, carpal tunnel syndrome, lumbar stenosis, herniated nucleus pulposus and the carcinoma. The pathophysiology of neuropathic pain are complex and not fully understood. Voltage gate sodium channel is a transmembrane protein, whose role in initiating the action potential and climbed impulses in nerve cells. VGSC are also involved in the dynamic regulation of nerve cell excitability. A disturbance or changes to the biophysical and VGSC expression would affect nerve cell excitability (Persson, 2009